Non-Traditional Exports (NTE), Imports and Economic Growth in Ghana - Antwi-Agyei, Percy (Graduate School of Business (GSB), 2024)
Non-traditional exports and imports in Ghana have grown in recent years thereby taking up a significant portion of the nation's international trade. This study investigates the relationship that non-traditional exports and imports have with Ghana's economic growth, using the Gross Domestic Product growth as the proxy for economic growth. The research used annual time series data from 1986 to 2020 and a quantitative research methodology. The empirical investigation was based on estimation techniques including unit root and the Autoregressive Distributed Lag (ARDL) regression estimation cointegration technique, together with diagnostic tests to assess the appropriateness of the model. The bounds test results showed the presence of cointegration between GDP growth and the NTEs as well as imports of Ghana within the period. The findings from the study showed that in the long run non-traditional exports have a positive insignificant relationship with the Gross Domestic Product growth. However, a positive significant relationship exists between NTE and economic growth in the short run. Imports have a positive and statistically significant relationship with economic growth in both the long run and the short run. Import trade impacted positively on the growth of the economy during the period under study. Gross Capital Formation also has a negative insignificant relationship with economic growth in both the short and long run. Inflation, however, showed an insignificant positive relationship with growth both in the long run and short run. The study therefore recommends that deliberate policy interventions and guidance aimed at improving the existing non-traditional export basket should be looked at and, in addition, explore avenues to increase the commodities in the non-traditional export basket to enhance economic growth.